Health profiles of adults with autism spectrum disorder: Differences between women and men. Issue 9 (2nd July 2021) - DaWalt, Leann Smith; Taylor, Julie Lounds; Movaghar, Arezoo; Hong, Jinkuk; Kim, Bryan; Brilliant, Murray; Mailick, Marsha R.
Abstract: The purpose of the present study was to investigate the hypothesis that women with autism have poorer health compared with men with autism, and compared with women without autism. Utilizing electronic health records drawn from a single health care system serving over 2 million individuals, 2119 adults with diagnosed autism spectrum disorders were compared with age‐ and sex‐matched controls. When considering health care utilization, we found evidence of multiplicative risk for conditions within some domains (i.e., nutrition conditions, neurologic disease, psychiatric conditions, and sleep disorders) such that women with autism spectrum disorder (ASD) experienced double jeopardy—meaning they had greater rates of health care utilization within a domain than what would separately be expected by virtue of being a woman and having ASD. For other domains (i.e., endocrine disorders, gastrointestinal disorders), the risk was additive such that being a female and having ASD were both associated with higher health care utilization, but there were no significant interaction effects. It was only with respect to one domain (cardiovascular) that rates of health care utilization were reflective of neither ASD diagnosis nor sex. Overall, our findings suggest that women with ASD are a vulnerable subgroup with high levels of health care utilization. Lay Summary: This study asked whether women with autism have poorer health compared with men with autism, and compared with women without autism. To answer this question, we used data from electronic health records. We found that women with autism spectrum disorder (ASD) were at the greatest risk for health problems such as nutrition conditions, neurologic disease, psychiatric conditions, and sleep disorders. More research on health of women with ASD is needed.